${{{{2.3}^{n + 1}} + {{7.3}^{n - 1}}} \over {{3^{n + 2}} - 2{{(1/3)}^{l - n}}}} = $
$1$
$3$
$-1$
$0$
${{{{[4 + \sqrt {(15)} ]}^{3/2}} + {{[4 - \sqrt {(15)} ]}^{3/2}}} \over {{{[6 + \sqrt {(35)} ]}^{3/2}} - {{[6 - \sqrt {(35)} ]}^{3/2}}}} = $
The value of $\sqrt {[12 - \sqrt {(68 + 48\sqrt 2 )} ]} = $
Solution of the equation $\sqrt {(x + 10)} + \sqrt {(x - 2)} = 6$ are
Number of Solution of the equation ${(x)^{x\sqrt x }} = {(x\sqrt x )^x}$ are
If ${a^{1/x}} = {b^{1/y}} = {c^{1/z}}$ and ${b^2} = ac$ then $x + z = $